2010
DOI: 10.1016/s1836-9553(10)70023-0
|View full text |Cite
|
Sign up to set email alerts
|

An inspiratory load enhances the antihypertensive effects of home-based training with slow deep breathing: a randomised trial

Abstract: NCT007919689.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
58
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 23 publications
0
58
0
3
Order By: Relevance
“…In a recent clinical trial, hypertensive patients practiced controlled breathing at 0.1 Hz with or without inspiratory load of 20 cmH 2 O for 8 weeks. Although blood pressure and heart rate decreased in both groups, a greater reduction in blood pressure (and a trend for heart rate) was observed for the group practicing with the inspiratory load (Jones, Sangthong, & Pachirat, ). These results, in addition to the findings of our experiment, suggest that applying inspiratory threshold load during controlled breathing at 0.1 Hz may enhance the effect of this breathing exercise on baroreflex function and cardiac vagal control when practiced for several weeks.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In a recent clinical trial, hypertensive patients practiced controlled breathing at 0.1 Hz with or without inspiratory load of 20 cmH 2 O for 8 weeks. Although blood pressure and heart rate decreased in both groups, a greater reduction in blood pressure (and a trend for heart rate) was observed for the group practicing with the inspiratory load (Jones, Sangthong, & Pachirat, ). These results, in addition to the findings of our experiment, suggest that applying inspiratory threshold load during controlled breathing at 0.1 Hz may enhance the effect of this breathing exercise on baroreflex function and cardiac vagal control when practiced for several weeks.…”
Section: Discussionmentioning
confidence: 84%
“…The low‐to‐moderate levels of dyspnea reported by our participants with the load of 10 cmH 2 O may be reduced by decreasing the duration of the exercise and by more frequent practice over time. Studies in hypertension patients using long‐term practice with loads of 18‒20 cmH 2 O have reported good compliance without any specific adverse events (Jones et al, ; Sangthong, Ubolsakka‐Jones, Pachirat, & Jones, ; Ubolsakka‐Jones, Sangthong, Khrisanapant, & Jones, ).…”
Section: Discussionmentioning
confidence: 99%
“…Inspiratory breathing loads can be used to examine breathing difficulty and generate respiratory-related evoked potentials with several peaks that indicate the transition from an early sensory component to a later cognitive aspect [23], [24], [25], [26]. Moreover, resistive loads generate pre-motor potentials that reflect the involvement of higher cortical motor areas [27], they decrease systolic blood pressure [28], they differ for males and females [29], they are perceived less intense in older individuals [30], they generate load-dependent increases of unpleasantness [31], and the subjective effects can be modified by attentional distractions [32]. Thus, inspiratory breathing load provides a powerful experimental approach to examine how optimal performers respond to the temporary perturbation of the internal body state.…”
Section: Introductionmentioning
confidence: 99%
“…Yoga and meditation are known to improve resting BP, and controlled slow breathing may be the common factor (Spicuzza, Gabutti, Porta, Montano, & Bernardi, ), and a number of experimental studies have shown benefits of slow breathing training for essential hypertension (Anderson, McNeely, & Windham, ; Grossman, Grossman, Schein, Zimlichman, & Gavish, ; Jones, Sangthong, & Pachirat, ; Logtenberg, Kleefstra, Houweling, Groenier, & Bilo, ; Mahtani, Nunan, & Heneghan, ; Meles et al, ). Although essential hypertension and ISH are assumed to have differing underlying causes, slow breathing training is also effective in reducing resting BP in ISH patients, and breathing with an inspiratory load is particularly effective (Sangthong, Ubolsakka‐Jones, Pachirat, & Jones, ).…”
Section: Introductionmentioning
confidence: 99%
“…Yoga and meditation are known to improve resting BP, and controlled slow breathing may be the common factor (Spicuzza, Gabutti, Porta, Montano, & Bernardi, 2000), and a number of experimental studies have shown benefits of slow breathing training for essential hypertension (Anderson, McNeely, & Windham, 2010;Grossman, Grossman, Schein, Zimlichman, & Gavish, 2001;Jones, Sangthong, & Pachirat, 2010;Logtenberg, Kleefstra, Houweling, Groenier, & Bilo, 2007;Mahtani, Nunan, & Heneghan, 2012;Meles et al, 2004).…”
mentioning
confidence: 99%